2018
DOI: 10.3892/etm.2018.6689
|View full text |Cite
|
Sign up to set email alerts
|

Suppression effect on IFN‑γ of adipose tissue‑derived mesenchymal stem cells isolated from β2‑microglobulin‑deficient mice

Abstract: Administration of bone marrow-derived mesenchymal stem cells (MSCs) is a possible treatment for graft-versus-host disease (GVHD) following allogeneic hematopoietic stem cell transplantation and other inflammatory conditions. To address the mechanism of immunosuppression by MSCs, in particular those derived from adipose tissue (AMSCs), AMSCs were isolated from three different mouse strains, and the suppressive capacity of the AMSCs thus obtained to suppress interferon (IFN)-γ generation in mixed lymphocyte reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Apoptosis and cell cycle arrest are two different mechanisms involved in the induction of cell death (Choi et al, 2018; Jung et al, 2019; Masuda et al, 2018; Salha et al, 2018; Zhang et al, 2010). We found increased apoptosis in T24 cells in the ADSC-CM groups than those in the T24-CM groups and that caspase 3/7 expression was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis and cell cycle arrest are two different mechanisms involved in the induction of cell death (Choi et al, 2018; Jung et al, 2019; Masuda et al, 2018; Salha et al, 2018; Zhang et al, 2010). We found increased apoptosis in T24 cells in the ADSC-CM groups than those in the T24-CM groups and that caspase 3/7 expression was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, B2M free, soluble HLA Class I molecules have been shown to inhibit the activity of activated T lymphocytes and even induce apoptosis of T cells 43 , 44 . Along the line, Masuda et al, have reported that adipose tissue-derived MSCs isolated from B2M-deficient mice display a potent capacity to suppress IFN-γ production 45 . It would be worth further investigation in a future study whether the actions of soluble HLA Class I molecules are the underlying mechanism of the enhanced inhibition to T cell proliferation associated with B2MKO iMSCs.…”
Section: Discussionmentioning
confidence: 99%